Cardiac autonomic responses induced by a single bout of exercise with flexible pole - Dos Santos António, Ana Márcia [UNESP] (2014)
Background: Flexible poles are tools used to provide rapid eccentric and concentric muscle contractions. It lacks in the literature studies that analyze acute cardiovascular responses in different exercises performed with this instrument. It was investigated the acute effects of exercise with flexible poles on heart period in healthy women. Methods. The study was performed on 32 women between 18 and 25 years old. It was evaluated the heart rate variability (HRV) in the time (SDNN, RMSSD and pNN50) and frequency domain (HF, LF and LF/HF ratio). The subjects remained at rest for 10 minutes. After the rest period, the volunteers performed the exercises with the flexible poles. Immediately after the exercise protocol, the volunteers remained seated at rest for 60 minutes and HRV were analyzed. Results: It was observed no significance changes in the time domain (SDNN: p = 0.14; RMSSD: p = 0.8 and pNN50: p = 0.86) and frequency domain indices (LF (nu): 0.4; LF (ms2): p = 0.34; HF (nu): p = 0.4; HF (ms2): p = 0.8 and LF/HF ratio: p = 0.3) between before and after single bout of exercise with flexible pole. Conclusion: A single bout of exercise with flexible pole did not significantly change cardiac autonomic regulation in healthy women.